Acceptable risk. [Season 1] [videorecording (DVD)] - Cassidy, Elaine, 1979-; Suurballe, Morten, 1955-; Ball, Angeline (RLJ Entertainment, 2017)
When an executive for a global pharmaceutical company, Gumbiner-Fishcher, is found dead in Montreal, his wife Sarah's world is thrown into a tailspin. With the ensuing investigation led by garda Emer Byrne revealing more questions than answers, Sarah suddenly finds herself under suspicion, and her life under surveillance.